2015
DOI: 10.21273/hortsci.50.3.461
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Soil Quality in Intensively Managed High Tunnel Vegetable Production Systems: A Role for Green Manures and Chicken Litter

Abstract: Use of high tunnel crop production is expected to increase to meet the growing demand for locally produced fresh market vegetables. These structures have the potential to offer many production benefits; however, managing soil quality in these structures is challenging and work in the area is limited. In this 3-year study, we compared the impacts of organic and inorganic fertility amendments on soil quality, nutrient availability, and the productivity of chard (Beta vulgaris L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 30 publications
0
30
1
1
Order By: Relevance
“…conventional conditions. Unlike in conventional production systems, where plants receive abundant supplies of inorganic fertilizers that are all readily available for plant uptake, plants in organic systems rely on organic fertility sources such as animal and plant residues that must mineralize before nutrients are available to plants (Hoagland et al, 2008;Rudisill et al, 2015;Reeve et al, 2016). Therefore, conducting breeding programs under organic conditions may favor selection for genotypes that are better able to support microbial symbionts like Trichoderma to help obtain nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…conventional conditions. Unlike in conventional production systems, where plants receive abundant supplies of inorganic fertilizers that are all readily available for plant uptake, plants in organic systems rely on organic fertility sources such as animal and plant residues that must mineralize before nutrients are available to plants (Hoagland et al, 2008;Rudisill et al, 2015;Reeve et al, 2016). Therefore, conducting breeding programs under organic conditions may favor selection for genotypes that are better able to support microbial symbionts like Trichoderma to help obtain nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, management practices commonly used in organic and conventional farming systems are well known for their potential to alter many soil properties 89 . For example, organic farmers commonly plant cover crops and apply organic fertility amendments, which increase soil organic matter and serve as the primary food and energy source for soil microbes 89 91 . Consequently, as the soil in the organic management system in this study had more active organic matter and a greater abundance of several types of soil microbial biomass including fungi (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The OC concentrations in mudflat saline soil at all DMA rates were following the increasing trend of tilled total biomass of green manures. Previous studies in cropland showed that tilled green manure increased soil OC concentration [25] and then improved soil aggregation status and decreased the bulk density [9], increased porosity [26], and saturated hydraulic conductivity [27]. Therefore, salinity reduction of mudflat saline soil might be attributed to the fact that OM enrichment by dairy manure combined with green manuring reduced soil bulk density, broke soil capillary, and suppressed salt solution rise through soil capillary [28,29].…”
Section: Discussionmentioning
confidence: 99%